HG removal from mercury-contaminated gas by AG-impregnated activated alumina adsorbents - Ebora, Jan Ralph; Manegdeg, Ferdinand G.; De Luna, Mark Daniel; Grisdanurak, Nurak (Philippine Engineering Journal)
Natural gas, a mixture of gaseous hydrocarbons, is used as fuel in various industrial and domestic applications. Unprocessed natural gas typically contains 1-400 µg/m3 toxic mercury vapor which damages pipes and equipment walls. In this study, novel silver impregnated activated alumina (Ag/AcAl) adsorbents were synthesized via ultrasound-assisted wet process. The adsorbents were used to remove elemental mercury (Hg0) from mercury-contaminated gas. Static adsorption experiments were carried out to evaluate the effects of dopant-to-support ratio, reaction temperature and contact time on (Hg0) removal. At 550C, up to 147.51 mg of Hg0 was removed per g of the 15% Ag/AcAl adsorbent after 40 days of static adsorption. In addition, dynamic adsorption experiments were conducted to compare the performance of the Ag/AcAl adsorbent and commercial activated carbon in removing elemental mercury from mercury contaminated gas stream. Results showed that Ag/AcAl was superior to activated carbon throughout the entire dynamic testing duration. This study demonstrates the potential of Ag/AcAl adsorbents for mercury removal from natural gas.